2013
DOI: 10.1088/0004-637x/763/2/119
|View full text |Cite
|
Sign up to set email alerts
|

An Interferometric Study of the Fomalhaut Inner Debris Disk. Ii. Keck Nuller Mid-Infrared Observations

Abstract: We report on high contrast mid-infrared observations of Fomalhaut obtained with the Keck Interferometer Nuller (KIN) showing a small resolved excess over the level expected from the stellar photosphere. The measured null excess has a mean value of 0.35% ± 0.10% between 8 and 11 µm and increases from 8 to 13 microns. Given the small field of view of the instrument, the source of this marginal excess must be contained within 2AU of Fomalhaut. This result is reminiscent of previous VLTI Kband (≃ 2µm) observations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 31 publications
3
45
1
Order By: Relevance
“…This means that not only the cross-section, but also the mass is dominated by barely bound grains in the innermost parts of the disk. Interestingly, such steep size distributions are also invoked to explain NIR interferometric observations of hot exozodiacal dust (Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013). The drop in the size distribution from β ≈ 0.5 to β ≈ 1 is also much more pronounced in the inner disk than in the parent belt.…”
Section: Size Distributionmentioning
confidence: 86%
See 2 more Smart Citations
“…This means that not only the cross-section, but also the mass is dominated by barely bound grains in the innermost parts of the disk. Interestingly, such steep size distributions are also invoked to explain NIR interferometric observations of hot exozodiacal dust (Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013). The drop in the size distribution from β ≈ 0.5 to β ≈ 1 is also much more pronounced in the inner disk than in the parent belt.…”
Section: Size Distributionmentioning
confidence: 86%
“…There are two additional problems with this scenario, which also serve as clues for solving the hot exozodiacal dust mystery. (1) Hot exozodiacal dust is thought to consist mostly of blowout grains with sizes around 0.01-0.1 µm (Akeson et al 2009;Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013), while P-R drag only transports bound grains to the sublimation zone, the smallest of which have sizes of about 1 µm. (2) The dust distribution resulting from the balance between P-R drag and collisions yields an SED with a positive slope in the infrared domain, while observations find negative slopes (e.g., Akeson et al 2009;Acke et al 2012), and the pile-up of dust is too inefficient to have an effect on the slope of the SED 15 .…”
Section: Other Explanations For Hot Exozodiacal Dustmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 shows that if all the circumstellar emission was located at the sublimation radius of micron-size carbonaceous grains, its diameter would only be about 5 mas and would therefore not be fully resolved. However, all the models that we have developed so far to reproduce resolved near-infrared detections of exozodiacal dust (Defrère et al 2011;Mennesson et al 2013;Lebreton et al 2013) have shown that most of the disc's thermal emission is produced at the sublimation distance of submicron grains, i.e., a region about 12 mas in diameter in the case of tet Per. We therefore expect that any dusty disc around tet Per would be fully resolved with FLUOR on the shortest baseline of the CHARA array.…”
Section: Exozodiacal Disc Modelmentioning
confidence: 99%
“…The sky transmission maps of the KIN and LBTI mid-IR nulling experiments are, on the other hand, much more complex in shape, and depend sensibly on observing parameters such as the observing date/time, and the parallactic and hour angles [e.g. 77,113]. The above 1D approach (Equation (4)) is therefore not appropriate, and it is necessary to multiply the synthetic 2D disc image in the sky plane with the 2D transmission map to obtain a synthetic null value.…”
Section: Spatial Distribution and Filteringmentioning
confidence: 99%